Adaptive negative impedance strategy for stability improvement in DC microgrid with constant power loads. (September 2021) - Kumar, Ramesh; Sharma, Rahul; Kumar, Ashwani
Highlights: This paper proposed adaptive virtual impedance to stabilize the DC microgrid by keeping virtual impedance dynamic. Stability improvement of DC microgrid under wide variation in CPL as compared to the existing techniques. The proposed scheme is contributed to improve the DC bus voltage regulation. The scheme provides better efficiency by improving the voltage regulation. Abstract: This paper presents a novel adaptive-based negative impedance strategy to solve the stability issue of DC microgrids with constant power loads (CPL). It is well known that constant power loads produce negative resistance characteristics, and its significance increases due the high penetration of CPL connected to a DC microgrid. The stability of DC power system starts deteriorating. Also, the stability problem becomes more sever if line inductance is not negligible. Therefore, the proposed strategy designed negative impedance at the source side of the converters which adapt the changes in CPL and DC link voltage deviations to adjust the parameters of negative impedance during live operation. The objectives of the proposed strategy are to provide improved stability margin as compared to the existing virtual negative stabilizer and reduces the voltage drop occurs in DC link voltage due to the consideration of the negative impedance. The adaptive virtual impedance is proposed to counteract the effect of large line inductance and CPL virtual resistance, thus enhancing the damping effect of the DC power system. The DC microgrid system with proposed strategy is carefully modeled using small signal analysis. Matlab Simulation is used to validate the effectiveness and the stable operation of a DC microgrid prototype with the proposed strategy under the variable CPL and the line impedance. Graphical abstract: Image, graphical abstract